Methods for calculating cartel damages: A survey - Anna Maria Doose (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2013)
The paper focuses on the various methods used to quantify cartel damages, which have become more and more important as private damage suits in the aftermath of antitrust litigation increase. The approaches implementation is embedded into current legal environments with regards to the estimation approaches being used for quantification of cartel damages. The direct comparison of methods shows that difference methods convince due to their simplicity and plausibility in results as well as replicability. Cost-based approaches have to overcome hurdles but still are easy to conduct and comparatively more accurate. In contrast, price prediction takes market changes into account and the market simulation presents the most sophisticated and flexible approach, provided that assumptions are correct and correctly implemented, and therefore approaches the real world counterfactual as approximate as possible.
Keywords: C10; C15; L12; L13; L4; K21; K41; 330; cartels; damages; antitrust policy; public enforcement; private enforcement